Phosphatidylinositol 4-Phosphate 5-Kinases 1 and 2 Are Involved in the Regulation of Vacuole Morphology During Arabidopsis Thaliana Pollen Development - (:unkn) unknown (ELSEVIER IRELAND LTD, 2016)
The pollen grains arise after meiosis of pollen mother cells within the anthers. A series of complex Structural changes follows, generating mature pollen grains capable of performing the double fertilization of the female megasporophyte. Several signaling molecules, including hormones and lipids, have been involved in the regulation and appropriate control of pollen development. Phosphatidylinositol 4-phophate 5-kinases (PIP5K), which catalyze the biosynthesis of the phosphoinositide Ptdlns(4,5)P-2, are important for tip polar growth of root hairs and pollen tubes, embryo development, vegetative plant growth, and responses to the environment. Here, we report a role of PIP5Ks during microgametogenesis. PIP5K1 and PIP5K2 are expressed during early stages of pollen development and their transcriptional activity respond to auxin in pollen grains. Early male gametophytic lethality to certain grade was observed in both pip5k1(-/-) and pip5k2(-/-) single mutants. The number of pip5k mutant alleles is directly related to the frequency of aborted pollen grains suggesting the two genes are involved in the same function. Indeed PIP5K1 and PIP5K2 are functionally redundant since homozygous double mutants did not render viable pollen grains. The loss of function of PIP5K1 and PIP5K2results in defects in vacuole morphology in pollen at the later stages and epidermal root cells. Our results show that PIP5K1, PIP5K2 and phosphoinositide signaling are important cues for early developmental stages and vacuole formation during microgametogenesis. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Pollen development; Microgametogenesis; Phosphoinositides; PIP5K; Vacuole